Transparent conductive film

By stacking a transparent conductive film of indium-tin composite oxide on a transparent plastic film substrate and controlling its resistance and surface resistance value distribution, the existing transparent conductive films have solved the shortcomings in pen pressurization durability and pen sliding durability, and achieved excellent position input and durability.

CN114930470BActive Publication Date: 2025-04-25TOYOBO CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202180008275.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-12-14
Filing Date
2021-03-26
Publication Date
2025-04-25
Estimated Expiration
2041-03-26

AI Technical Summary

Technical Problem

The existing transparent conductive film is insufficient in the pen pressurization durability test, and higher pen sliding durability and position input are required in the resistive film type touch panel.

Method used

By laminating a transparent conductive film of indium-tin composite oxide on a transparent plastic film substrate, the on-resistance is controlled to be less than 10 kΩ, the increase rate of the surface resistance value is less than 1.5, and it is maintained at less than 20% in the evaluation of the surface resistance value distribution to improve the pen sliding durability and pen pressurization durability.

Benefits of technology

It realizes excellent pen sliding durability and pen pressurization durability of transparent conductive films, while maintaining excellent position input, and is suitable for use in resistive film-type touch panels and other purposes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114930470B_ABST
    Figure CN114930470B_ABST
Patent Text Reader

Abstract

A transparent conductive film is a transparent conductive film in which a transparent conductive film of an indium-tin composite oxide is laminated on at least one surface of a transparent plastic film substrate, wherein the on-resistance of the transparent conductive film based on a pen sliding durability test is 10 kΩ or less, the increase rate of the surface resistance value of the transparent conductive film based on a pen weight pressure test is 1.5 or less, and the surface resistance value distribution evaluation is 20% or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a transparent conductive film having a transparent conductive film of a crystalline indium-tin composite oxide laminated on a transparent plastic film substrate, and more particularly to a transparent conductive film having excellent pen sliding durability, excellent pen weight pressure durability, and excellent position input performance when used in a resistive film type touch panel. Background Art

[0002] A transparent conductive film, which is a thin film with low resistance and transparent laminated on a transparent plastic substrate, is widely used in the electrical and electronic fields for applications utilizing its conductivity, such as transparent electrodes for flat panel displays such as liquid crystal displays and electroluminescent (EL) displays, and touch panels.

[0003] For example, a resistive film touch panel is a combination of a fixed electrode coated with a transparent conductive film on a glass or plastic substrate and a movable electrode (= membrane electrode) coated with a transparent conductive film on a plastic film, which are overlapped on the upper side of a display body for use. Pressing the membrane electrode with a finger or a pen causes the fixed electrode and the transparent conductive film of the membrane electrode to contact each other, which serves as input for position recognition of the touch panel.

[0004] For example, as a means of improving the pen sliding durability, there is a method of making the transparent conductive thin film on the membrane electrode side crystalline (see Patent Document 1).

[0005] Prior Art Literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent Application Publication No. 2004-071171 Summary of the invention

[0008] -Problems to be solved by the invention-

[0009] The conventional transparent conductive film shown in Patent Document 1 attempts to improve the pen sliding durability by controlling the crystallinity of indium-tin composite oxide. However, the conventional transparent conductive film is insufficient when subjected to the pen weight pressure durability test described later. In addition, in recent years, the use of resistive film touch panels has become diverse, and further improvement of the pen sliding durability is required.

[0010] Compared with fingers, pens often apply a stronger force to the touch panel. If the touch panel is continuously input with a pen, cracks, peeling, abrasion, and other damage may occur on the transparent conductive film on the membrane electrode side. In addition, if the touch panel is violently hit with a pen or the pen input is performed with a very strong force, a strong force greater than that normally assumed is applied to the touch panel, cracks, peeling, and other damage may occur on the transparent conductive film.

[0011] In order to solve these problems, a transparent conductive film having both excellent pen sliding durability and excellent pen weight pressure durability is urgently desired. Furthermore, it is necessary to improve these durability while satisfying excellent input performance. Therefore, of course, in a resistive film touch panel, a transparent conductive film having excellent position input performance is urgently desired.

[0012] In view of the above-mentioned conventional problems, an object of the present invention is to provide a transparent conductive film which has excellent pen sliding durability and pen weight pressure durability when used for a touch panel and further has excellent position input properties.

[0013] -Methods for solving the problem-

[0014] The present invention has been made in view of the above-mentioned circumstances, and the transparent conductive film of the present invention that can solve the above-mentioned problems has the following structure.

[0015] [1] A transparent conductive film, comprising a transparent conductive film of indium-tin composite oxide laminated on at least one surface of a transparent plastic film substrate, wherein the on-resistance of the transparent conductive film in the following pen sliding durability test is 10 kΩ or less, the rate of increase of the surface resistance value of the transparent conductive film in the following pen weight pressure test is 1.5 or less, and further, the following surface resistance value distribution evaluation is 20% or less.

[0016] (Pen sliding durability test method)

[0017] The transparent conductive film involved in the present invention is used as one panel, and as the other panel, a transparent conductive film composed of an indium-tin composite oxide thin film (tin oxide content: 10% by mass) is used. The indium-tin composite oxide thin film is formed on a glass substrate by sputtering and has a thickness of 20nm. The two panels are arranged with epoxy beads of 30μm in diameter so that the transparent conductive films are opposite to each other, and the panel on the film side and the panel on the glass side are pasted with a double-sided tape of 170μm thickness to make a touch panel. Next, a load of 2.5N is applied to a polyacetal pen (shape of the front end: 0.8mmR), and a linear sliding test of 180,000 reciprocations is performed on the touch panel. In this test, the load of the pen is applied to the transparent conductive film surface involved in the present invention.

[0018] The sliding distance at this time was 30 mm and the sliding speed was 180 mm / sec. After the sliding durability test, the on-resistance (resistance value when the movable electrode (membrane electrode) and the fixed electrode are in contact) when the sliding part is pressed with a pen load of 0.8 N was measured.

[0019] (Pen weight pressure test method)

[0020] The transparent conductive film of the present invention cut into 50mm×50mm is used as one panel, and as the other panel, a transparent conductive film composed of an indium-tin composite oxide film (tin oxide content: 10% by mass) is used. The indium-tin composite oxide film is formed on a glass substrate by sputtering and has a thickness of 20nm. The two panels are arranged with epoxy beads of 30μm in diameter so that the transparent conductive films are opposite to each other, and the panel on the film side is pasted to the panel on the glass side by a double-sided tape adjusted to a thickness of 120μm to make a touch panel. A polyacetal pen (the shape of the front end is 0.8mmR) is used to apply a load of 35N to a position 2.0mm away from the end of the double-sided tape, and a linear slide is performed 10 times (reciprocating 5 times) in parallel with the double-sided tape. In this test, the load of the pen is applied to the transparent conductive film surface involved in the present invention. The sliding distance at this time is 30mm, and the sliding speed is 20mm / second. Slide at a position without epoxy beads. After sliding, remove the transparent conductive film, measure the surface resistance of any five locations of the sliding part (4-terminal method), and find the average value. When measuring the surface resistance, arrange four terminals in a direction perpendicular to the sliding part, and the sliding part comes between the second terminal and the third terminal. Divide the average value of the surface resistance value of the sliding part by the surface resistance value of the non-sliding part (measured by the 4-terminal method) to calculate the increase rate of the surface resistance value.

[0021] (Surface resistance distribution evaluation)

[0022] The transparent conductive film roll was cut into 330 mm in the longitudinal direction (MD) and the cut film was heat treated at 165° C. for 75 minutes. The surface resistance values ​​at 12 points in the heat treated transparent conductive film were measured, and the surface resistance value distribution was calculated by Formula 1.

[0023] [(Maximum value of surface resistance) - (Minimum value of surface resistance)] ÷ (Maximum value of surface resistance) × 100 (Formula 1)

[0024] [2] A transparent conductive film according to the above [1], wherein the grain size of the transparent conductive film of the indium-tin composite oxide film is 10 to 100 nm, the crystallinity of the transparent conductive film of the indium-tin composite oxide film is 20 to 80%, the transparent conductive film of the indium-tin composite oxide film comprises 0.5 to 10% by mass of tin oxide, the thickness of the transparent conductive film of the indium-tin composite oxide film is 10 to 30 nm, the three-dimensional surface roughness SRa of the transparent conductive film of the indium-tin composite oxide film is 1 to 100 nm, and the thickness distribution of the transparent conductive film in the width (TD) direction is less than 5%.

[0025] (Evaluation of Thickness Distribution in the Width (TD) Direction of Transparent Conductive Film)

[0026] The transparent conductive film roll was cut into 50 mm lengths in the length (MD) direction. The thickness of the cut film was measured every 50 mm in the width (TD) direction from the end of the end in the width (TD) direction until the opposite end, and the thickness distribution of the transparent conductive film was calculated using Formula 2.

[0027] {(maximum value of the thickness of the transparent conductive film) - (minimum value of the thickness of the transparent conductive film)} ÷ (maximum value of the thickness of the transparent conductive film) × 100 (Formula 2)

[0028] In addition, the distance between the opposite end portion and the measurement position a point in front of it may be less than 50 mm.

[0029] [3] The transparent conductive film according to [1] or [2] above, wherein the transparent conductive film does not peel off in an adhesion test relative to the surface of the transparent conductive film (JIS K5600-5-6: 1999), and in a bending resistance test relative to the transparent conductive film side of the transparent conductive film relative to the indium-tin composite oxide (JIS K5600-5-1: 1999), the diameter of the mandrel that causes cracking or peeling when the bent portion is observed with a 10x magnifying glass is less than 20 mm.

[0030] [4] The transparent conductive film according to any one of [1] to [3] above, wherein the transparent conductive film has a thickness of 100 to 250 μm.

[0031] [5] The transparent conductive film according to any one of [1] to [4], comprising a curable resin layer between the transparent conductive film of indium-tin composite oxide and the transparent plastic film substrate.

[0032] -Effects of the Invention-

[0033] According to the transparent conductive film of the present invention, excellent pen sliding durability and excellent pen weight pressing durability are achieved simultaneously, and further, excellent position input performance is exhibited. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 This is a schematic diagram showing an example (part 1) of the longest part of a crystal grain in the present invention.

[0035] Figure 2 This is a schematic diagram showing another example (part 2) of the longest portion of a crystal grain in the present invention.

[0036] Figure 3 This is a schematic diagram showing another example (part 3) of the longest part of the crystal grain in the present invention.

[0037] Figure 4 This is a schematic diagram showing another example (fourth) of the longest part of the crystal grain in the present invention.

[0038] Figure 5 This is a schematic diagram for explaining the position of a center roll of an example of a sputtering device preferably used in the present invention.

[0039] Figure 6 This is a schematic diagram showing an example of a test piece used for evaluating the surface resistance value distribution. DETAILED DESCRIPTION

[0040] The transparent conductive film of the present invention is a transparent conductive film in which a transparent conductive film of an indium-tin composite oxide is laminated on at least one surface of a transparent plastic film substrate, and the on-resistance of the transparent conductive film obtained by the following pen sliding durability test is 10 kΩ or less, and the rate of increase of the surface resistance value of the transparent conductive film obtained by the following pen weight pressure test is 1.5 or less. Furthermore, the following surface resistance value distribution evaluation is 20% or less.

[0041] (Pen sliding durability test)

[0042] The transparent conductive film involved in the present invention is used as one panel, and as the other panel, a transparent conductive film composed of an indium-tin composite oxide thin film (tin oxide content: 10% by mass) is used. The indium-tin composite oxide thin film is formed on a glass substrate by sputtering and has a thickness of 20nm. The two panels are arranged with epoxy beads of 30μm in diameter so that the transparent conductive films are opposite to each other, and the panel on the film side and the panel on the glass side are pasted with a double-sided tape of 170μm thickness to make a touch panel. Next, a load of 2.5N is applied to a polyacetal pen (shape of the front end: 0.8mmR), and a linear sliding test of 180,000 reciprocations is performed on the touch panel. In this test, the load of the pen is applied to the transparent conductive film surface involved in the present invention. The sliding distance at this time is 30mm, and the sliding speed is 180mm / second. After the sliding durability test, the on-resistance (resistance value when the movable electrode (membrane electrode) contacts the fixed electrode) when the sliding part is pressed with a pen load of 0.8N is measured.

[0043] (Pen weight pressure test)

[0044] A transparent conductive film cut into 50 mm × 50 mm is used as one panel, and a transparent conductive film composed of an indium-tin composite oxide thin film (tin oxide content: 10 mass %) is used as another panel. The indium-tin composite oxide thin film is formed on a glass substrate by sputtering and has a thickness of 20 nm. The two panels are arranged with epoxy beads of 30 μm in diameter so that the transparent conductive films are opposite to each other, and the panel on the film side is pasted to the panel on the glass side by a double-sided tape adjusted to a thickness of 120 μm to make a touch panel. A polyacetal pen (the shape of the front end is 0.8 mmR) is used to apply a load of 35 N to a position 2.0 mm away from the end of the double-sided tape, and a linear slide is performed 10 times (reciprocating 5 times) in parallel with the double-sided tape. In this test, the load of the pen is applied to the transparent conductive film surface involved in the present invention. The sliding distance at this time is 30 mm, and the sliding speed is 20 mm / second. Among them, sliding is performed at a position without epoxy beads. After sliding, remove the transparent conductive film, measure the surface resistance of any five locations of the sliding part (4-terminal method), and find the average value. When measuring the surface resistance, arrange four terminals in a direction perpendicular to the sliding part, and the sliding part comes between the second terminal and the third terminal. Divide the average value of the surface resistance value of the sliding part by the surface resistance value of the non-sliding part (measured by the 4-terminal method) to calculate the increase rate of the surface resistance value.

[0045] (Surface resistance distribution evaluation)

[0046] The transparent conductive film roll was cut into 330 mm in the longitudinal direction (MD) and the cut film was heat treated at 165° C. for 75 minutes. The surface resistance values ​​of 12 black dots in the heat treated transparent conductive film were measured, and the surface resistance value distribution was calculated by Formula 1.

[0047] {(maximum surface resistance value) - (minimum surface resistance value)} ÷ (maximum surface resistance value) × 100 (Formula 1)

[0048] Here, the details of the 12-point black dot portion are as described later. Figure 6 That's an example.

[0049] The transparent conductive film of the present invention has excellent pen sliding durability and pen weight pressure durability. In addition, it has excellent position input performance. The obtained transparent conductive film is extremely useful for applications such as resistive film touch panels.

[0050] Pen sliding durability and pen weight pressure durability are opposite properties. First, the pen sliding durability is described. The transparent conductive film of indium-tin composite oxide with excellent pen sliding durability requires the transparent conductive film to have high crystallinity and large grain size, and then the three-dimensional surface roughness of the transparent conductive film is small. The three-dimensional surface roughness will be described later, and the crystallinity and grain size will be described first. The portion with circular or polygonal areas observed under a transmission electron microscope is defined as crystals (= grains) of the transparent conductive film, and the other portion is defined as amorphous. High crystallinity means a high proportion of crystals. A large grain size means that the circular or polygonal area observed under a transmission electron microscope is large. The transparent conductive film with high crystallinity has a high proportion of hard crystals, a large strain around the grains with a large grain size, etc., so the transparent conductive film becomes hard and has excellent pen sliding durability.

[0051] According to the present invention, the transparent conductive film of the present invention disposed on the membrane electrode side can suppress damage such as cracks, peeling, and wear even when input is continuously performed on the touch panel using a pen.

[0052] Of course, the present invention can also have excellent sliding durability in finger input on the touch panel.

[0053] Next, the durability against pen weight pressure is described. The transparent conductive film of the indium-tin composite oxide having excellent durability against pen weight pressure has low crystallinity and small grain size. The transparent conductive film with low crystallinity has a high proportion of soft amorphous and small grain size, and the strain around the grains becomes small. Therefore, even if a load is applied to the transparent conductive film, cracks are unlikely to occur, and thus the durability against pen weight pressure is excellent.

[0054] Compared with fingers, a pen often applies a stronger force to the touch panel. According to the present invention, even if the pen input has excellent durability against the pen weight pressure, even if the pen input is continuously applied to the touch panel, the transparent conductive film of the present invention disposed on the membrane electrode side can be prevented from being damaged by cracks, peeling, abrasion, etc.

[0055] Of course, the present invention can also have excellent heavy pressure durability in finger input to the touch panel.

[0056] As described above, it is known that the pen sliding durability and the pen weight pressing durability are opposite properties. As a result of the study, it is found that the pen sliding durability and the pen weight pressing durability can be achieved by controlling the crystallinity and grain size of the transparent conductive film.

[0057] Furthermore, the present invention can provide a transparent conductive film having excellent position input properties. Therefore, accurate position input properties can be exhibited in various display devices. In particular, it is extremely useful for applications such as resistive film touch panels.

[0058] Hereinafter, a transparent conductive film which can achieve both pen sliding durability and pen weight pressing durability and also has a transparent conductive film that exhibits accurate position input properties will be described.

[0059] In the present invention, if the on-resistance of the transparent conductive film of the transparent conductive film based on the pen sliding durability test is 10 kΩ or less, even if the touch panel is continuously inputted with a pen, cracks, peeling, wear, etc. with respect to the transparent conductive film can be suppressed, so it is preferred. In one embodiment, the on-resistance may be 9.5 kΩ or less, and more preferably 5 kΩ or less. For example, the on-resistance is 3 kΩ or less, and may be 1.5 kΩ or less, and preferably 1 kΩ or less.

[0060] The on-resistance is preferably a smaller value, for example, it may be 5 kΩ or more, or 3 kΩ or more. In one embodiment, it is 0 kΩ or more, for example, 0.05 kΩ or more.

[0061] By setting the on-resistance to be within such a range, even when input is continuously performed on the touch panel with a pen, cracks, peeling, abrasion, etc. on the transparent conductive film can be suppressed.

[0062] In one embodiment, these upper limits and lower limits may be appropriately combined.

[0063] In the present invention, the rate of increase of the surface resistance value of the transparent conductive film based on the pen weight pressure test is preferably 1.5 or less. By having such a characteristic, for example, even if a strong force greater than that normally assumed is applied, cracks, peeling, etc. can be suppressed in the transparent conductive film. More preferably, the rate of increase of the surface resistance value is 1.2 or less, and particularly preferably 1.0 (no increase).

[0064] Here, the increase rate of the surface resistance value of the transparent conductive film according to the present invention is preferably 1.0 or more.

[0065] In one embodiment, the on-resistance of the transparent conductive film based on a pen sliding durability test is greater than or equal to 0.05 kΩ and less than or equal to 9.5 kΩ, and the increase rate of the surface resistance value of the transparent conductive film based on a pen weight pressure (durability) test is greater than or equal to 1.0 and less than or equal to 1.5.

[0066] As described above, generally, the pen sliding durability and the pen weight pressure durability are opposite properties. In the present invention, within such a range, these two durability can be balanced. In addition, even if the touch panel is continuously input with a pen, cracks, peeling, wear, etc. can be suppressed with respect to the transparent conductive film, and excellent durability can be exhibited against the load of pen sliding and pen weight pressure. In addition, the numerical range can be selected from the range and value recorded in this specification.

[0067] The transparent conductive film in the present invention is preferably one that does not peel off even when an adhesion test (JIS K5600-5-6: 1999) is performed on the transparent conductive film surface. A transparent conductive film that does not peel off in the adhesion test is preferably one that is in close contact with a transparent plastic substrate, a curable resin layer, or other layers that are in contact with the transparent conductive film, and therefore, even when input is continuously made to the touch panel using a pen, cracks, peeling, abrasion, etc. can be suppressed with respect to the transparent conductive film. Furthermore, even when a strong force greater than that assumed in normal use is applied, cracks, peeling, etc. can be suppressed with respect to the transparent conductive film.

[0068] The transparent conductive film of the present invention preferably has a crystal size of 10 to 100 nm and a crystallinity of 20 to 80% for the transparent conductive film of indium-tin composite oxide. When the crystal size of the transparent conductive film of indium-tin composite oxide is 10 nm or more, the transparent conductive film becomes moderately hard due to the strain around the crystal grains of the transparent conductive film, and thus the pen sliding durability is excellent, which is preferred. More preferably, the crystal size of the transparent conductive film of indium-tin composite oxide is 30 nm or more.

[0069] On the other hand, if the crystal grain size of the transparent conductive film of the indium-tin composite oxide is 100 nm or less, the transparent conductive film will not be too hard due to the strain around the crystal grains of the transparent conductive film, and thus the durability against pen weight pressure is excellent, which is preferred. More preferably, the crystal grain size of the transparent conductive film of the indium-tin composite oxide is 90 nm or less.

[0070] In one embodiment, the crystal size of the transparent conductive film of the indium-tin composite oxide is 10 nm to 95 nm, for example, 30 nm to 90 nm, for example, 40 nm to 80 nm.

[0071] For example, in the grain size observed under a transmission electron microscope, the longest part of all the grains is measured, and the average value of the measured values ​​is taken as the grain size. Figures 1 to 4 2 shows an example of a method for identifying the longest part when measuring the longest part of a crystal grain.

[0072] When the crystallinity of the transparent conductive film of indium-tin composite oxide is 20% or more, it is moderately hard due to the hard crystals occupying the transparent conductive film, and the pen sliding durability is excellent, so it is preferred. More preferably, the crystallinity of the transparent conductive film of indium-tin composite oxide is 25% or more. On the other hand, when the crystallinity of the transparent conductive film of indium-tin composite oxide is 80% or less, the amount of hard crystals included is large, but since the transparent conductive film is not too hard, the pen weight pressure durability is excellent, so it is preferred.

[0073] In one embodiment, the crystallinity of the transparent conductive film of the indium-tin composite oxide is 25% to 78%, for example, 25% to 76%.

[0074] The transparent conductive film in the present invention preferably has a three-dimensional surface roughness SRa of 1 to 100 nm. If the three-dimensional surface roughness SRa of the transparent conductive film is 1 to 100 nm, the surface protrusions of the transparent conductive film are small, so the deformation of the surface protrusions during the pen weight pressure test is reduced, which suppresses the generation of cracks in the transparent conductive film. Furthermore, there are a few surface protrusions on the transparent conductive film, so the film rollability can be maintained, which is preferred. It is more preferred that the three-dimensional surface roughness SRa of the transparent conductive film is 1 to 80 nm. It is further preferred that the three-dimensional surface roughness SRa of the transparent conductive film is 1 to 65 nm.

[0075] The transparent conductive film in the present invention is composed of an indium-tin composite oxide, preferably including 0.5% by mass or more and 10% by mass or less of tin oxide. Tin oxide in the indium-tin composite oxide is equivalent to an impurity for indium oxide. By containing tin oxide impurities, the melting point of the indium-tin composite oxide increases. That is, since the impurity content of tin oxide acts in the direction of hindering crystallization, it is an important factor with a strong correlation with crystallinity such as grain size and crystallinity. If 0.5% by mass or more of tin oxide is contained, the surface resistance of the transparent conductive film becomes a practical level and is preferred. More preferably, the content of tin oxide is 1% by mass or more, and particularly preferably 2% by mass or more. If the content of tin oxide is 10% by mass or less, crystallization is easy to occur on the basis of adjusting to the semi-crystalline state described later, and the pen sliding durability becomes good and preferred. The content of tin oxide is more preferably 8% by mass or less, further preferably 6% by mass or less, and particularly preferably 4% by mass or less. In addition, the surface resistance of the transparent conductive film of the present invention is preferably 50 to 900Ω / □, and more preferably 50 to 600Ω / □.

[0076] In the present invention, the thickness of the transparent conductive film is preferably greater than 10nm and less than 30nm. The thickness of the transparent conductive film is an important factor that has a strong correlation with crystallinity such as grain size and crystallinity. If the thickness of the transparent conductive film is greater than 10nm, the amorphous content of the transparent conductive film will not be too much, and it is easy to give the appropriate grain size and crystallinity that will become a semi-crystalline state described later, and as a result, the pen sliding durability is maintained, which is preferred. It is more preferred that the thickness of the transparent conductive film is greater than 13nm, and more preferably greater than 16nm. In addition, if the thickness of the transparent conductive film is less than 30nm, the grain size of the transparent conductive film will not be too large, the crystallinity will not be too high, and it is easy to maintain a semi-crystalline state, and it is preferred to maintain the pen weight pressure durability. It is more preferred to be less than 28nm, and further preferably less than 25nm.

[0077] The transparent conductive film in the present invention is preferably subjected to a bending resistance test (JIS K5600-5-1: 1999) on the transparent conductive film side of the transparent conductive film, and the mandrel diameter that causes cracking and peeling when the bent portion is observed with a 10x magnifying glass is less than 20 mm. If the mandrel diameter is less than 20 mm, the layer in contact with the transparent conductive film will not break when a pen weight pressure test is performed, and no cracks will be generated in the transparent conductive film, so it is preferred. More preferably, it is 18 mm or less. In one embodiment, the value of the bending resistance test is, for example, 15 mm or more, can be 8 mm or more, and is preferably 1 mm or more.

[0078] The thickness of the transparent plastic film substrate of the transparent conductive film in the present invention is preferably in the range of 100 to 250 μm, more preferably 130 to 220 μm. If the thickness of the plastic film is 100 μm or more, the mechanical strength is maintained, especially when used for a touch panel, the deformation relative to the pen input is small, and the pen sliding durability and pen weight pressure durability are excellent, so it is preferred. On the other hand, when the thickness is 250 μm or less, when used for a touch panel, it is not necessary to increase the load for positioning by pen input, which is preferred.

[0079] The transparent conductive film in the present invention preferably has a curable resin layer between the transparent conductive film of indium-tin composite oxide and the plastic film substrate.

[0080] The presence of the curable resin layer can increase the adhesion of the transparent conductive film and disperse the force applied to the transparent conductive film, thereby suppressing cracks, peeling, and wear of the transparent conductive film in a pen sliding test. Furthermore, cracks, peeling, and the like can be suppressed in a pen weight pressure test, and therefore it is preferred.

[0081] The crystallinity of the transparent conductive film in the present invention is in a state of being too high or too low (such crystallinity is called semi-crystalline or semi-crystalline). It is very difficult to stabilize the transparent conductive film and make it semi-crystalline. The reason is that the state of stopping halfway during the rapid phase transition from amorphous to crystalline is semi-crystalline. Therefore, it is sensitive to the parameter related to crystallinity, that is, the amount of water in the film-forming atmosphere, and in particular, it is very sensitive to the gas containing hydrogen atoms. Even if the gas containing hydrogen atoms and the amount of water in the film-forming atmosphere are slightly less, it will become almost completely crystalline (high crystallinity). On the contrary, if the gas containing hydrogen atoms and the amount of water in the film-forming atmosphere are slightly more, it will become amorphous (low crystallinity).

[0082] The transparent conductive film of the present invention is a transparent conductive film in which a transparent conductive film of an indium-tin composite oxide is laminated on at least one surface of a transparent plastic film substrate, and the surface resistance distribution is 20% or less.

[0083] (Surface resistance distribution evaluation)

[0084] The transparent conductive film roll was cut into 330 mm in the longitudinal direction (MD) and the cut film was heat treated at 165° C. for 75 minutes. The surface resistance values ​​at 12 points in the heat treated transparent conductive film were measured, and the surface resistance value distribution was calculated by Formula 1.

[0085] For example, the transparent conductive film after heat treatment can also be measured. Figure 6 The surface resistance distribution of the 12 black dot portions was calculated using Formula 1.

[0086] [(Maximum value of surface resistance) - (Minimum value of surface resistance)] ÷ (Maximum value of surface resistance) × 100 (Formula 1)

[0087] According to the transparent conductive film of the present invention, Figure 6 The film has a good surface resistance value over the entire surface, so that the touch panel can have a more uniform surface resistance over a wide area, and can exhibit excellent input properties and more accurate input characteristics.

[0088] Thus, according to the present invention, cracks, peeling, abrasion, etc. can be suppressed relative to the transparent conductive film in the pen sliding test, and further, cracks, peeling, abrasion, etc. can also be suppressed relative to the transparent conductive film in the pen weight pressure test. Moreover, according to the present invention, it is possible to show excellent surface resistance value distribution and excellent input properties. Therefore, it can be used for touch panels of various sizes. For example, it can be well used for touch panels of about 20 inches from a touch panel of about 3.5 inches, especially for resistive film touch panels.

[0089] If the surface resistance value distribution of the transparent conductive film of the present invention is 20% or less, when the transparent conductive film is applied to the resistive film touch panel, accurate position input can be performed, so it is preferred. For example, the surface resistance value distribution is 19%, it can be 18% or less, preferably 17% or less. For example, the surface resistance value distribution can also be 16% or less.

[0090] The surface resistance value distribution is preferably close to 0%, for example, 10% or more, may be 5% or more, and preferably 0% or more. In one embodiment, these upper limits and lower limits may be appropriately combined.

[0091] The transparent conductive film of the present invention is semi-crystalline. The semi-crystalline state in the present invention is a state where a rapid phase change from amorphous to crystalline is stopped in the middle.

[0092] The inventors of the present invention have succeeded in maintaining uniform semi-crystallinity over the entire surface of the transparent conductive film while making the transparent conductive film semi-crystalline. As a result, the surface resistance distribution has been successfully controlled within a given range by making the transparent conductive film semi-crystalline as described in the present invention and making the thickness distribution in the width (TD) direction of the transparent conductive film more uniform.

[0093] The thickness distribution of the transparent conductive film of the present invention in the width (TD) direction is preferably 5% or less. The thickness distribution of the transparent conductive film in the width (TD) direction can be evaluated by the following method.

[0094] (Evaluation of Thickness Distribution in the Width (TD) Direction of Transparent Conductive Film)

[0095] The transparent conductive film roll was cut into 50 mm pieces in the length (MD) direction. The thickness of the cut film was measured every 50 mm from the end in the width (TD) direction to the opposite end, and the thickness distribution of the transparent conductive film was calculated using Formula 2.

[0096] {(maximum value of the thickness of the transparent conductive film) - (minimum value of the thickness of the transparent conductive film)} ÷ (maximum value of the thickness of the transparent conductive film) × 100 (Formula 2)

[0097] In addition, the distance between the opposite end portion and the point in front of 1 may be less than 50 mm.

[0098] When the thickness distribution in the width (TD) direction of the transparent conductive film of the present invention is large, the surface resistance value distribution tends to increase. The reasons are as follows. In order to manufacture the transparent conductive film with high productivity, it is preferred to use a roll-to-roll sputtering device. If a film roll (transparent plastic film substrate) with a large thickness distribution in the width (TD) direction is placed in a roll-to-roll sputtering device, water and organic gases fall off unevenly relative to the width (TD) direction of the film in the film roll. In other words, when a transparent conductive film is formed on the film, the amount of water and organic gas released from the film in the width (TD) direction of the film is different. In addition, if there are too much water and organic gas, the crystallinity of the transparent conductive film will be reduced, which may cause changes in semi-crystallinity. As a result, since there is a tendency to change the surface resistance value, if the thickness distribution in the width (TD) direction is large, the uniformity of the semi-crystallinity of the transparent conductive film in the width (TD) direction of the film is lost, and the surface resistance value distribution tends to increase.

[0099] However, the effects of the present invention cannot be obtained simply by including the thickness distribution of the transparent conductive film in the width (TD) direction within a given range. That is, in the present invention, the evaluation results of the pen sliding durability test and the evaluation results of the pen weight pressure durability test are also included in the scope of the present invention, thereby making it possible to further exert various effects derived from, for example, the surface resistance value distribution.

[0100] If the thickness distribution in the width (TD) direction of the transparent conductive film of the present invention is 5% or less, water and / or organic gas will fall off uniformly from the film roll in the width (TD) direction of the film in the film roll in a sputtering device, such as a roll-to-roll sputtering device. As a result, the semi-crystallinity becomes more uniform and the surface resistance value distribution becomes smaller, which is preferred. For example, the thickness distribution in the width (TD) direction of the transparent conductive film can be 4.8% or less, preferably 4.5% or less.

[0101] The thickness distribution in the width (TD) direction of the transparent conductive film is preferably as small as possible, and is, for example, 3% or more, may be 1% or more, and is preferably 0% or more. In one embodiment, these upper limits and lower limits may be appropriately combined.

[0102] The production method for obtaining the transparent conductive film of the present invention is not particularly limited, and for example, the following production methods can be preferably exemplified.

[0103] As a method for forming a transparent conductive film of a crystalline indium-tin composite oxide on at least one surface of a transparent plastic film substrate, a sputtering method is preferably used. In order to manufacture a transparent conductive film with high productivity, it is preferred to use a so-called roller sputtering device in the shape of supplying a film roll and winding the film roll after film formation. In the film forming atmosphere, a gas containing hydrogen atoms (as long as it is a gas containing hydrogen atoms such as hydrogen, ammonia, hydrogen + argon mixed gas, there is no particular limitation, wherein water is excluded) is introduced into the amount described below in a mass flow controller, and then, the film temperature during sputtering is set to below 0°C, and a sintered target of an indium-tin composite oxide containing 0.5 to 10% by mass of tin oxide is used, and the thickness of the transparent conductive film of the indium-tin composite oxide is adjusted to 10 to 30 nm, and a transparent conductive film is formed on a transparent plastic film having a three-dimensional surface roughness SRa of 1 to 100 nm of the transparent conductive film of the indium-tin composite oxide. In the film forming atmosphere during sputtering, the gas containing hydrogen atoms has the effect of hindering the crystallization of the transparent conductive film. When hydrogen gas is passed through the film formation atmosphere, the value of (hydrogen flow rate)÷(inert gas flow rate+hydrogen flow rate)×100 (sometimes simply described as hydrogen concentration) is preferably 0.01 to 3.00%. The hydrogen concentration is, for example, 0.01% to 2.00%, or 0.01% to 1.00%.

[0104] By setting the hydrogen concentration within such a range, for example, it is possible to contribute to obtaining good results in any of the on-resistance value of a pen sliding durability test and the pen weight pressing durability test.

[0105] In addition, as inert gases, helium, neon, argon, krypton, xenon, etc. can be cited. When the hydrogen concentration is 0.01 to 3.00%, the transparent conductive film becomes semi-crystalline, so it is preferred. In the case of using a gas containing hydrogen atoms other than hydrogen, the amount of hydrogen atoms included in the gas containing hydrogen atoms can be converted into the amount of hydrogen (= hydrogen molecules) for calculation. When the gas containing hydrogen atoms is precisely flowed in the film-forming atmosphere by a mass flow controller, by configuring the gas outlet so that the gas containing hydrogen atoms can be evenly blown in a direction perpendicular to the length direction of the film roller, it is easy to obtain a transparent conductive film that is difficult to become a transparent conductive film with a high crystallinity portion and a low crystallinity portion mixed, and a uniform semi-crystalline transparent conductive film, so that a transparent conductive film with excellent pen sliding durability and pen weight pressure durability can be appropriately obtained. It is known that if there is a lot of water in the film-forming atmosphere, the crystallinity of the transparent conductive film is reduced, so the amount of water in the film-forming atmosphere is also an important factor.

[0106] When water and organic gas generated from the film are generated unevenly from within the film surface, the semi-crystallinity of the transparent conductive film becomes uneven, and as a result, there is a tendency for the surface resistance value distribution to increase. As a countermeasure using the manufacturing method, it is preferred to continuously form at least two layers of transparent conductive film on a film roll.

[0107] In one embodiment, the precursor of the transparent conductive film is formed until the thickness of the precursor of the transparent conductive film is 35 to 65% of the total thickness of the transparent conductive film. In the present invention, the precursor of the transparent conductive film obtained under such conditions is referred to as a seed layer.

[0108] Furthermore, when a gas containing hydrogen atoms is used in the formation of the seed layer, it is preferable to control the central value X of the ratio of the partial pressure of water to the inert gas in the film formation atmosphere during sputtering onto the film roll (partial pressure of water / partial pressure of inert gas), that is, the value between the maximum value and the minimum value of the above ratio, to 1.00×10 -3 ~4.80×10 -3 .

[0109] The precursor of the transparent conductive film is formed into a film until the thickness of the precursor of the transparent conductive film is 35 to 65% of the total thickness of the transparent conductive film, that is, the transparent conductive film is formed on the substrate film by forming a film seed layer, thereby being able to fully suppress the generation of water and organic gas generated from the film, and being able to fully reduce the unevenness of the amount of water and / or organic gas generated from various locations within the surface of the film.

[0110] In addition, when using a gas containing hydrogen atoms, by controlling X to 1.00×10 -3 ~4.80×10 -3 The seed layer is used as a seed layer for growing a highly uniform semi-crystalline transparent conductive film in the film surface of the present invention. The seed layer may be a single layer or may be two or more layers.

[0111] Next, when a transparent conductive film is formed on the seed layer until the thickness of the transparent conductive film reaches the target total thickness of the transparent conductive film, when a gas containing hydrogen atoms is used, it is preferred that the central value Y of the ratio of the partial pressure of water to the inert gas (partial pressure of water / partial pressure of inert gas) in the film-forming atmosphere during sputtering onto the seed layer, i.e., the value between the maximum value and the minimum value of the ratio, is controlled to 0.15×10 -3 ~0.90×10 -3 .

[0112] Furthermore, it is preferred to control the average Z of X and Y to 0.58×10 -3 ~2.80×10 -3 . On the seed layer, the transparent conductive film may be one layer or two or more layers. As a result, a semi-crystalline transparent conductive film with high uniformity in the film surface can be obtained. In addition, a semi-crystalline transparent conductive film with high uniformity in the transparent conductive film surface is obtained, and the surface resistance value distribution becomes low. Furthermore, with respect to Z, if the difference between the maximum value and the minimum value from the beginning of film formation to the end of film formation is 1.00×10 -3Hereinafter, the uniformity of the crystallinity of the transparent conductive film is maintained over the entire length of the film. For example, in addition to the rotary pump, turbomolecular pump, and cryogenic pump that are often used as exhaust devices of sputtering machines, if the amount of water released from the film during the formation of the transparent conductive film is reduced in the bombardment process described below, the height difference of the concave and convex end surface of the film roller described below is limited, and a protective film with low water absorption is pasted on the opposite side of the surface of the film-forming transparent conductive film, etc., and a uniform amount of water is released over the entire length of the film, then precise control of the amount of water is not required, and therefore it is preferred. Among them, Z also depends on the content of tin oxide in the transparent conductive film of indium-tin composite oxide, the thickness of the transparent conductive film, etc. In the case where the amount of tin oxide added in the transparent conductive film of indium-tin composite oxide is large, the transparent conductive film is thin, etc., it is preferred to set Z to be lower in the above range. On the contrary, in the case where the content of tin oxide in the transparent conductive film of indium-tin composite oxide is low, in the case where the transparent conductive film is thicker, etc., it is preferred to set Z, which is the central value of the ratio of the partial pressure of water to the inert gas, to be higher in the above range.

[0113] The transparent conductive film is preferably formed on the transparent plastic film with the film temperature during sputtering being set to 0° C. or less. The film temperature during film formation is replaced by the set temperature of a temperature controller that adjusts the temperature of a center roll that contacts the traveling film.

[0114] Here, Figure 5 A schematic diagram showing an example of a sputtering device preferably used in the present invention, in which a film 1 is traveling while partially contacting the surface of a center roller 2. An indium-tin sputtering target 4 is set via a chimney 3, and a thin film of indium-tin composite oxide is deposited and laminated on the surface of the film 1 traveling on the center roller 2. Each target is separated by a separator 5. The center roller 2 is temperature-controlled by a temperature controller not shown. If the film temperature is below 0°C, the release of impurity gases such as water and organic gases from the film that scatter the crystallinity of the transparent conductive film can be suppressed, so that the crystallinity of the transparent conductive film from the beginning to the end of film formation is easily uniformed, which is preferred. When using a gas containing hydrogen atoms, the average Z of X and Y is preferably 0.58×10 -3 ~2.80×10 -3 . If Z is within the above range, the hindrance of the crystallinity of the transparent conductive film caused by the gas containing hydrogen atoms effectively works, so it is preferred. In addition, in order to make the surface resistance and total light transmittance of the transparent conductive film reach a practical level, it is preferred to add oxygen during sputtering. This manufacturing method mainly tries to eliminate the influence of crystallinity caused by water, which is an important factor that scatters the crystallinity of the transparent conductive film, and uses hydrogen-containing gas to control the crystallinity.

[0115] In controlling the moisture content when forming an indium-tin composite oxide on a plastic film, it is preferable to actually observe the moisture content during film formation rather than to observe the achieved vacuum degree for the following two reasons.

[0116] The first reason is that when a film is formed on a plastic film by sputtering, the film is heated and moisture is released from the film, so the moisture content in the film-forming atmosphere increases, which is greater than the moisture content measured when the vacuum degree is reached. Therefore, it is more accurate to express it in terms of the moisture content when the film is formed than in terms of the vacuum degree reached.

[0117] The second reason is the case of an apparatus that throws in a large amount of transparent plastic film. In such an apparatus, the film is thrown in in the form of a film roll. If the film is thrown into a vacuum tank as a roll, the water on the outer layer of the roll is easy to fall off, but the water on the inner layer of the roll is difficult to fall off. This is because the film roll stops when measuring the vacuum degree reached, but the film roll moves during film formation, so the inner layer of the film roll including a large amount of water is rolled out, and thus the moisture content in the film forming atmosphere increases, compared to the moisture content when the vacuum degree reached is measured. In the present invention, when controlling the moisture content in the film forming atmosphere, it is possible to preferably deal with it by observing the ratio of the water partial pressure of the film forming atmosphere during sputtering to the inert gas.

[0118] Preferably, before forming the transparent conductive film, the film is subjected to a bombardment process. The so-called bombardment process refers to the process of applying a voltage to discharge and generate plasma in a state where only an inert gas such as argon or a mixed gas of a reactive gas such as oxygen and an inert gas flows. Specifically, it is preferred to join the film by RF sputtering using a SUS target or the like. Since the film is exposed to the plasma by the bombardment process, water and organic components are released from the film, and the water and organic components released from the film when the transparent conductive film is formed are reduced, so that the crystallinity of the transparent conductive film from the beginning of film formation to the end of film formation is easily uniformized, and the crystallinity within the surface of the transparent conductive film of the transparent conductive film is easily uniformized, so it is preferred. In addition, since the layer to which the transparent conductive film is connected is activated by the bombardment process, the adhesion of the transparent conductive film is improved, so the pen sliding durability and the pen weight pressure durability are improved, so it is preferred.

[0119] The height difference between the most convex part and the most concave part of the film roller for forming the transparent conductive film is preferably 10 mm or less. If it is 10 mm or less, when the film roller is put into the sputtering device, the unevenness of the release method of water and organic components from the film end surface becomes small, so that the crystallinity of the transparent conductive film from the beginning of film formation to the end of film formation is easy to be uniform, and the crystallinity of the transparent conductive film in the surface of the transparent conductive film is easy to be uniform, so it is preferred.

[0120] In the film (transparent plastic film substrate) for forming a transparent conductive film, it is preferred to paste a protective film with low water absorption on the opposite side of the surface on which the transparent conductive film is formed. By pasting a protective film with low water absorption, it is not easy to release water and other gases from the film substrate. As a result, the unevenness in the method of releasing water and other gases becomes smaller, so the crystallinity of the transparent conductive film from the beginning of film formation to the end of film formation is easy to be uniform, and the crystallinity within the surface of the transparent conductive film of the transparent conductive film is easy to be uniform, so it is preferred. As the substrate of the protective film with low water absorption, polyethylene, polypropylene, cycloolefin, etc. are preferred.

[0121] In the method of forming a transparent conductive film of a crystalline indium-tin composite oxide on at least one surface of a transparent plastic film substrate, it is preferred to introduce oxygen during sputtering. If oxygen is introduced during sputtering, there will be no adverse conditions due to the lack of oxygen in the transparent conductive film of the indium-tin composite oxide, and the surface resistance of the transparent conductive film is low, and the total light transmittance becomes high, which is preferred. Therefore, in order to make the surface resistance and total light transmittance of the transparent conductive film reach a practical level, it is preferred to introduce oxygen during sputtering. In addition, the total light transmittance of the transparent conductive film of the present invention is preferably 70 to 95%.

[0122] The transparent conductive film of the present invention is preferably formed by laminating a transparent conductive film of an indium-tin composite oxide on a transparent plastic film substrate, and then preferably subjected to a heat treatment at 80 to 200° C. for 0.1 to 12 hours in an atmosphere including oxygen. If it is 80° C. or higher, it is easy to slightly improve the crystallinity in order to form a semi-crystalline state, and the pen sliding durability is improved, so it is preferred. If it is 200° C. or lower, it is preferred to ensure the planarity of the transparent plastic film.

[0123] <Transparent plastic film substrate>

[0124] The transparent plastic film substrate used in the present invention refers to a film obtained by melt-extruding an organic polymer in a film form or by extruding a solution, and stretching, cooling, and heat-fixing in the length direction and / or width direction as needed. Examples of the organic polymer include polyethylene, polypropylene, polyethylene terephthalate, polyethylene 2,6-naphthalate, polytrimethylene terephthalate, polybutylene terephthalate, nylon 6, nylon 4, nylon 66, nylon 12, polyimide, polyamide-imide, polyether sulfone, polyether ether ketone, polycarbonate, polyarylate, cellulose propionate, polyvinyl chloride, polyvinylidene chloride, polyvinyl alcohol, polyetherimide, polyphenylene sulfide, polyphenylene ether, polystyrene, syndiotactic polystyrene, and norbornene-based polymers.

[0125] Among these organic polymers, preferred are polyethylene terephthalate, polytrimethylene terephthalate, polybutylene terephthalate, polyethylene-2,6-naphthalate, syndiotactic polystyrene, norbornene polymers, polycarbonate, polyarylate, etc. In addition, these organic polymers may be copolymerized with a small amount of monomers of other organic polymers, or may be blended with other organic polymers.

[0126] The transparent plastic film substrate used in the present invention may be subjected to surface activation treatment such as corona discharge treatment, glow discharge treatment, flame treatment, ultraviolet irradiation treatment, electron beam irradiation treatment, ozone treatment, etc., within the range not impairing the purpose of the present invention.

[0127] If a curable resin layer is coated on a transparent plastic film substrate, the transparent conductive film can be firmly in close contact with the curable resin layer and disperse the force applied to the transparent conductive film, so that cracks, peeling, wear, etc. are suppressed relative to the transparent conductive film in the pen sliding test, and further, cracks, peeling, etc. are suppressed relative to the transparent conductive film in the pen weight pressure test, so it is preferred. In addition, if a transparent conductive film is formed on the basis of making the surface of the curable resin layer concave and convex, the actual contact area when the transparent conductive film contacts the glass during the pen sliding test is reduced, so the sliding property of the glass surface and the transparent conductive film is improved, the pen sliding durability is improved, and the improvement of the winding property of the film roller and the anti-Newton ring property can be expected, but if the concave and convex are too large, the deformation amount of the surface protrusion during the pen weight pressure test becomes large, and cracks are generated on the transparent conductive film, so it is not preferred. Therefore, as the surface concave and convex, the three-dimensional surface roughness SRa of the transparent conductive film is preferably 1 to 100nm. The following describes the details of the curable resin layer.

[0128] In addition, as the curable resin preferably used in the present invention, there is no particular limitation as long as it is a resin that is cured by energy application such as heating, ultraviolet irradiation, electron beam irradiation, etc., and examples thereof include silicone resins, acrylic resins, methacrylic resins, epoxy resins, melamine resins, polyester resins, polyurethane resins, etc. From the viewpoint of productivity, it is preferred to use ultraviolet curable resins as the main component.

[0129] As such ultraviolet curable resins, for example, there can be mentioned polyfunctional acrylate resins such as polyfunctional acrylic acid or methacrylate of polyols, polyfunctional urethane acrylate resins synthesized from diisocyanates, polyols, and hydroxyalkyl esters of acrylic acid or methacrylate, etc. As required, monofunctional monomers such as vinyl pyrrolidone, methyl methacrylate, styrene, etc. can be added to these polyfunctional resins for copolymerization.

[0130] In addition, in order to improve the adhesion between the transparent conductive film and the curable resin layer, it is effective to treat the surface of the curable resin layer by the following method. Specific methods include: discharge treatment method of irradiating glow or corona discharge to increase carbonyl, carboxyl, and hydroxyl groups; chemical treatment method of treating with acid or alkali to increase polar groups such as amino, hydroxyl, and carbonyl groups, etc.

[0131] Ultraviolet curing resins are usually used by adding a photopolymerization initiator. As the photopolymerization initiator, a known compound that absorbs ultraviolet rays and generates free radicals can be used without particular limitation. Examples of such photopolymerization initiators include various benzoins, phenyl ketones, and benzophenones. The amount of the photopolymerization initiator added is usually preferably 1 to 5 parts by mass relative to 100 parts by mass of the ultraviolet curing resin.

[0132] In addition, in the present invention, in addition to the curing resin as the main component, inorganic particles and organic particles are preferably used in the curing resin layer. By dispersing the inorganic particles and organic particles in the curing resin, it is possible to form concavities and convexities on the curing resin surface and improve the surface roughness in a wide area.

[0133] Examples of the inorganic particles include silica, etc. Examples of the organic particles include polyester resins, polyolefin resins, polystyrene resins, and polyamide resins.

[0134] In addition to inorganic particles and organic particles, in addition to the curable resin as the main component, it is also preferred to use a resin that is incompatible with the curable resin. By using a small amount of incompatible resin in the curable resin of the matrix, phase separation can be caused in the curable resin, and the incompatible resin can be dispersed in the form of particles. The dispersed particles of the incompatible resin can form unevenness on the surface of the curable resin, thereby improving the surface roughness in a wide area.

[0135] Examples of the incompatible resin include polyester resin, polyolefin resin, polystyrene resin, and polyamide resin.

[0136] Here, as an example, the mixing ratio when using inorganic particles in the curable resin layer is shown: 0.1 to 20 parts by mass of inorganic particles are preferred, 0.1 to 15 parts by mass are more preferred, and 0.1 to 12 parts by mass are particularly preferred per 100 parts by mass of the ultraviolet curable resin.

[0137] If the amount of the inorganic particles added is 0.1 to 20 parts by mass per 100 parts by mass of the UV-curable resin, the protrusions formed on the surface of the curable resin layer are too small, which can effectively impart three-dimensional surface roughness. When a pen weight pressure test is performed, the deformation of the surface protrusions becomes smaller, thereby suppressing the occurrence of cracks in the transparent conductive film. Furthermore, since there are a few surface protrusions on the transparent conductive film, the rollability of the film can be maintained, which is preferred.

[0138] The ultraviolet curable resin, photopolymerization initiator, inorganic particles, organic particles, and non-miscible resins of the ultraviolet curable resin are dissolved in a common solvent to prepare a coating liquid. The solvent used is not particularly limited, for example, alcohol solvents such as ethanol and isopropanol, ester solvents such as ethyl acetate and butyl acetate, ether solvents such as dibutyl ether and ethylene glycol monoethyl ether, ketone solvents such as methyl isobutyl ketone and cyclohexanone, aromatic hydrocarbon solvents such as toluene, xylene, and solvent naphtha, etc. can be used alone or in combination. The more the amount of solvent added to dissolve the ultraviolet curable resin, photopolymerization initiator, inorganic particles, organic particles, and non-miscible resins of the ultraviolet curable resin, in other words, the lower the solid concentration, the smaller the thickness distribution of the curable resin layer, so it is preferred.

[0139] The concentration of the resin component in the coating liquid can be appropriately selected in consideration of the viscosity corresponding to the coating method. For example, the total amount of the ultraviolet curable resin, the photopolymerization initiator, and the high molecular weight polyester resin in the coating liquid is usually 20 to 80% by mass. In addition, other known additives, such as silicone leveling agents, etc., can also be added to the coating liquid as needed.

[0140] In the present invention, the prepared coating liquid is applied to a transparent plastic film substrate. The coating method is not particularly limited, and conventionally known methods such as bar coating, gravure coating, and reverse coating can be used.

[0141] The solvent of the coating liquid after application is evaporated and removed in the subsequent drying process. In this process, the high molecular weight polyester resin uniformly dissolved in the coating liquid becomes particles and precipitates in the ultraviolet curing resin. After the coating film is dried, the plastic film is irradiated with ultraviolet rays, thereby crosslinking and curing the ultraviolet curing resin to form a curing resin layer. In this curing process, the particles of the high molecular weight polyester resin are fixed in the hard coating layer, and protrusions are formed on the surface of the curing resin layer, which improves the surface roughness in a wide area.

[0142] In addition, the thickness of the curable resin layer is preferably in the range of 0.1 to 15 μm. More preferably, it is in the range of 0.5 to 10 μm, and particularly preferably in the range of 1 to 8 μm. When the thickness of the curable resin layer is 0.1 μm or more, it is preferred to form sufficient protrusions. On the other hand, if it is 15 μm or less, productivity is good, so it is preferred. In addition, the thickness distribution of the curable resin layer is preferably less than 5%.

[0143] Example

[0144] Hereinafter, the present invention will be described in further detail by way of examples, but the present invention is not limited to these examples. In addition, various measurements and evaluations in the examples were performed by the following methods.

[0145] (1) Total light transmittance

[0146] The total light transmittance was measured using NDH-2000 manufactured by Nippon Denshoku Industries, Ltd. in accordance with JIS-K7361-1:1997.

[0147] (2) Surface resistance

[0148] The measurement was performed using a four-probe method in accordance with JIS-K7194: 1994. As the measuring machine, Lotesta AX MCP-T370 manufactured by Mitsubishi Chemical Analytech Co., Ltd. was used.

[0149] (3) Average surface roughness SRa of the three-dimensional center plane

[0150] The three-dimensional center plane average surface roughness SRa is given by ISO 25178, and the three-dimensional center plane average surface roughness SRa is obtained using a three-dimensional surface shape measuring device, Burt Scan (R5500H-M100 manufactured by Ryoka Systems Co., Ltd. (measurement conditions: wave mode, measurement wavelength 560nm, objective lens 10 times)). The number of measurements is set to 5, and their average value is obtained. Here, the first decimal place of the nm unit is rounded off.

[0151] (4) Grain size

[0152] A film sample with a laminated transparent conductive thin film layer was cut into a size of 1 mm x 10 mm and pasted on the upper surface of a suitable resin block with the conductive thin film facing outward. After trimming, ultrathin slices roughly parallel to the film surface were prepared using a general ultrathin microtome technique.

[0153] The slice was observed with a transmission electron microscope (JEM-2010 manufactured by JEOL), and a portion of the surface of the conductive film without significant damage was selected and photographed at an accelerating voltage of 200 kV and a direct magnification of 40,000 times.

[0154] In the crystal grains observed under a transmission electron microscope, the longest part of all the crystal grains was measured, and the average value of the measured values ​​was taken as the crystal grain size. Figures 1 to 4 An example of a method for identifying the longest portion when measuring the longest portion of a crystal grain is shown in . That is, the longest portion is identified based on the length of a straight line that can maximally measure the grain size of each crystal grain.

[0155] (5) Thickness of transparent conductive film (film thickness)

[0156] The film sample piece laminated with the transparent conductive thin film layer was cut into a size of 1mm×10mm and embedded in epoxy resin for electron microscopy. It was fixed on the sample holder of the ultra-thin slicer to make a cross-sectional thin section parallel to the short side of the embedded sample piece. Next, a transmission electron microscope (JEOL, JEM-2010) was used to take photos of the film without significant damage at an accelerating voltage of 200kV and a bright field at an observation magnification of 10,000 times, and the film thickness was obtained from the obtained photos.

[0157] (6) Pen sliding durability test

[0158] The transparent conductive film involved in the present invention is used as one panel, and as the other panel, a transparent conductive film composed of an indium-tin composite oxide thin film (tin oxide content: 10% by mass) is used. The indium-tin composite oxide thin film is formed on a glass substrate by sputtering and has a thickness of 20nm. The two panels are arranged with epoxy beads of 30μm in diameter so that the transparent conductive films are opposite to each other to make a touch panel. Next, a load of 2.5N is applied to a polyacetal pen (shape of the front end: 0.8mmR), and a linear sliding test of 180,000 reciprocating strokes is performed on the touch panel. In this test, the load of the pen is applied to the transparent conductive film surface involved in the present invention. The sliding distance at this time is 30mm, and the sliding speed is 180mm / second. After the sliding durability test, the on-resistance (resistance value when the movable electrode (membrane electrode) contacts the fixed electrode) when the sliding part is pressed with a pen load of 0.8N is measured. The on-resistance is preferably less than 10kΩ.

[0159] In addition, in the comparative examples, the film in each comparative example was used instead of the transparent conductive film according to the present invention.

[0160] (7) Pen weight pressure test

[0161] The transparent conductive film involved in the present invention was cut into a transparent conductive film of 50mm×50mm and used as one panel, and a transparent conductive film composed of an indium-tin composite oxide thin film (tin oxide content: 10% by mass) was used as the other panel. The indium-tin composite oxide thin film was formed on a glass substrate by sputtering and had a thickness of 20nm. The two panels were arranged with epoxy beads of 30μm in diameter so that the transparent conductive films were opposite to each other, and the panel on the film side was pasted to the panel on the glass side with a double-sided tape adjusted to a thickness of 120μm to make a touch panel. A load of 35N was applied to a position 2.0mm away from the end of the double-sided tape using a polyacetal pen (the shape of the front end was 0.8mmR), and a linear slide was performed 10 times (reciprocating 5 times) in parallel with the double-sided tape. In this test, the load of the pen was applied to the transparent conductive film surface involved in the present invention. The sliding distance at this time was 30mm, and the sliding speed was 20mm / second. Among them, sliding was performed at a position without epoxy beads. After sliding, remove the transparent conductive film, measure the surface resistance of any five locations of the sliding part (4-terminal method), and find the average value. When measuring the surface resistance, arrange four terminals in a direction perpendicular to the sliding part, and the sliding part comes between the second terminal and the third terminal. Divide the average value of the surface resistance value of the sliding part by the surface resistance value of the non-sliding part (measured by the 4-terminal method) to calculate the increase rate of the surface resistance value.

[0162] In addition, in the comparative examples, the film in each comparative example was used instead of the transparent conductive film according to the present invention.

[0163] (8) Measurement of the Content of Tin Oxide in Transparent Conductive Film

[0164] Cut the sample (about 15cm 2 ), add 20 ml of 6 mol / l hydrochloric acid to a quartz conical flask, and seal the film without volatilization of the acid. Leave it for 9 days at room temperature while shaking it frequently to dissolve the transparent conductive film. Take out the residual film, and use the hydrochloric acid in which the transparent conductive film is dissolved as the measurement liquid. In and Sn in the dissolved liquid are obtained by the calibration curve method using an ICP emission analyzer (manufacturer name: Rigaku, device model: CIROS-120EOP). The measurement wavelength of each element is selected to have a high sensitivity without interference. In addition, the standard solution is used by diluting the commercially available standard solution of In and Sn.

[0165] (9) Adhesion test

[0166] Implemented in accordance with JIS K5600-5-6:1999.

[0167] (10) Bending resistance test

[0168] The test was conducted in accordance with JIS K5600-5-1: 1999. However, when the mandrel diameter did not break or peel off to 13 mm, the bending resistance test was not conducted and all the diameters were recorded as 13 mm.

[0169] (11) Evaluation of surface resistance distribution

[0170] The transparent conductive film roll was cut into 330 mm in the longitudinal direction (MD). The cut film was heat-treated at 165° C. for 75 minutes. Figure 6 The surface resistance values ​​of the 12 black dots are used to calculate the surface resistance value distribution using Formula 1.

[0171] {(maximum surface resistance value) - (minimum surface resistance value)} ÷ (maximum surface resistance value) × 100 (Formula 1)

[0172] (12) Evaluation of Thickness Distribution in the Width (TD) Direction of Transparent Conductive Film

[0173] The transparent conductive film roll was cut into 50 mm in the longitudinal direction (MD). The thickness of the cut film was measured every 50 mm in the width direction (TD) from the end of the end in the width direction (TD), and the thickness was measured until the opposite end, and the thickness distribution of the transparent conductive film was calculated using Formula 2. However, there was a case where the interval between the opposite end and the point before the end was less than 50 mm.

[0174] The thickness of the transparent conductive film is measured with a micrometer.

[0175] [(maximum value of the thickness of the transparent conductive film) - (minimum value of the thickness of the transparent conductive film)] ÷ (maximum value of the thickness of the transparent conductive film) × 100 (Formula 2)

[0176] The transparent plastic film substrate used in the examples and comparative examples is a biaxially oriented transparent PET film (manufactured by Toyobo Co., Ltd., A4340, thickness is recorded in Table 1) having an easy-adhesive layer on both sides. 100 parts by mass of an acrylic resin containing a photopolymerization initiator as a curable resin layer (manufactured by Dainichi Seika Industries, SEIKA Beam (registered trademark) EXF-01J) is mixed with the amount of silica particles recorded in Table 1 (manufactured by Nissan Chemical Co., Ltd., SNOWTEXZL), and a mixed solvent of toluene / MEK (8 / 2: mass ratio) is added as a solvent to the solid concentration recorded in Table 1A and Table 2A, and stirred to make it uniformly dissolved to prepare a coating liquid (hereinafter, the coating liquid is referred to as coating liquid A). The prepared coating liquid is applied using a Meyer rod so that the average thickness of the coating film at any 5 points is 5 μm. After drying at 80°C for 1 minute, the sample was irradiated with ultraviolet light (light intensity: 300 mJ / cm 2 ) to cure the coating. In addition, the curable resin layer is provided on both sides of the transparent plastic substrate.

[0177] (Examples 1 to 8)

[0178] Each example level was carried out under the conditions shown in Table 1 as follows.

[0179] Place the membrane in the vacuum tank and evacuate to 1.5×10 -4 Pa. Next, after the oxygen was introduced, argon gas as an inert gas and hydrogen gas as a hydrogen-containing gas were introduced at the concentrations shown in Table 1 so that the total pressure became 0.6 Pa.

[0180] At 4.5W / cm 2 Electric power is applied to a sintered target of indium-tin composite oxide or a sintered target of indium oxide without tin oxide, and a seed layer is formed by a DC magnetron sputtering method, followed by a transparent conductive film. The film thickness is controlled by changing the speed at which the film passes over the target. In addition, a gas analyzer (manufactured by Inficon, Transpector XPR3) is used to measure the ratio of the water partial pressure of the film-forming atmosphere to the inert gas during sputtering. In each embodiment level, in order to adjust the ratio X, Y of the water partial pressure of the film-forming atmosphere to the inert gas during sputtering and the average Z of X and Y, as described in Table 1, the presence or absence of a bombardment process, the presence or absence of a protective film, the height difference of the concave and convex end face of the film roller, and the temperature of the heat medium of the temperature controller that controls the temperature of the center roller where the film contacts the travel are adjusted. The temperature exactly in the middle of the maximum and minimum values ​​of the temperature from the beginning of film formation on the film roller to the end of film formation is recorded in Table 1 as the center value.

[0181] The film in which the transparent conductive film was laminated was subjected to the heat treatment described in Table 1, and then the measurement was performed. Table 1 shows the measurement results.

[0182] (Comparative Examples 1 to 11)

[0183] Under the conditions described in Table 1, a transparent conductive film was prepared and evaluated in the same manner as in Example 1. In Comparative Example 7, no curable resin layer was provided. In Comparative Example 8, the thickness of the coating film of the curable resin layer was adjusted to 20 μm. The results are shown in Table 2.

[0184] [Table 1A]

[0185]

[0186] [Table 1B]

[0187]

[0188] [Table 2A]

[0189]

[0190] [Table 2B]

[0191]

[0192] As shown in Table 1, the transparent conductive films described in Examples 1 to 8 exhibited pen sliding durability, pen weight pressing durability, and excellent position input properties.

[0193] However, as shown in Table 2, Comparative Examples 1 to 11 cannot achieve both pen sliding durability and pen weight pressing durability. In addition, there are also comparative examples that lack position input performance.

[0194] -Industrial Availability-

[0195] As described above, according to the present invention, a transparent conductive film having excellent pen sliding durability, pen weight pressure durability, and accurate position input performance can be produced, which is extremely useful for applications such as resistive film touch panels.

[0196] -Explanation of symbols-

[0197] 1. Membrane

[0198] 2. Center roller

[0199] 3. Chimney

[0200] 4. Indium-tin composite oxide target

[0201] 5. Chamber.

Claims

1. A transparent conductive film, A transparent conductive film of indium-tin composite oxide is laminated on at least one surface of a transparent plastic film substrate, wherein the on-resistance of the transparent conductive film in the following pen sliding durability test is 10 kΩ or less, The rate of increase in the surface resistance value of the transparent conductive film in the following pen weight pressure test is 1.5 or less, Furthermore, the following surface resistance distribution evaluation is 20% or less, In the pen sliding durability test method, The transparent conductive film is used as one panel, and a transparent conductive film composed of an indium-tin composite oxide thin film is used as the other panel. The indium-tin composite oxide thin film is formed on a glass substrate by sputtering and has a thickness of 20 nm, wherein the tin oxide content is 10% by mass. The two panels were arranged with epoxy beads of 30 μm in diameter interposed therebetween so that the transparent conductive films faced each other, and the film-side panel and the glass-side panel were adhered to each other with a double-sided tape of 170 μm in thickness to produce a touch panel. Next, a polyacetal pen was subjected to a 180,000-reciprocating linear sliding test on the touch panel with a load of 2.5 N applied. The tip of the pen had a shape of 0.8 mmR. In this test, the load of the pen was applied to the transparent conductive film surface. The sliding distance at this time was 30 mm, and the sliding speed was 180 mm / sec. After the pen sliding durability test, the on-resistance when the sliding part was pressed with a pen load of 0.8 N was measured. The on-resistance is the resistance value when the membrane electrode as the movable electrode contacts the fixed electrode. In the pen weight pressure test method, The transparent conductive film cut into 50 mm×50 mm was used as one panel, and a transparent conductive thin film composed of an indium-tin composite oxide film was used as the other panel. The indium-tin composite oxide film was formed on a glass substrate by sputtering and had a thickness of 20 nm, wherein the tin oxide content was 10% by mass. The two panels were arranged with epoxy beads of 30 μm in diameter interposed therebetween so that the transparent conductive films faced each other, and the film-side panel and the glass-side panel were adhered to each other using a double-sided tape adjusted to a thickness of 120 μm to produce a touch panel. A load of 35 N was applied to a position 2.0 mm from the end of the double-sided tape using a polyacetal pen, and linear sliding was performed 10 times, i.e., 5 times of reciprocation, in parallel with the double-sided tape. The shape of the tip of the pen was 0.8 mmR. In this test, the load of the pen was applied to the transparent conductive film surface, the sliding distance at this time was 30 mm, and the sliding speed was 20 mm / sec. Slide at a position without epoxy beads, remove the transparent conductive film after sliding, measure the surface resistance of 5 random points of the sliding part by the 4-terminal method, and calculate the average value. When measuring the surface resistance, four terminals are arranged in a direction perpendicular to the sliding part so that the sliding part comes between the second terminal and the third terminal. The average surface resistance value of the sliding part was divided by the surface resistance value of the non-sliding part measured by the four-terminal method to calculate the increase rate of the surface resistance value. In the surface resistance distribution evaluation, The transparent conductive film roll was cut to 330 mm in the length MD direction. The cut film was heated at 165°C for 75 minutes. The surface resistance values ​​at 12 points in the transparent conductive film after the heat treatment were measured, and the surface resistance value distribution was calculated by Formula 1: [(maximum value of surface resistance) - (minimum value of surface resistance)] ÷ (maximum value of surface resistance) × 100 (Formula 1).

2. The transparent conductive film according to claim 1, wherein The crystal size of the transparent conductive film of the indium-tin composite oxide is 10 to 100 nm, and the crystallinity of the transparent conductive film of the indium-tin composite oxide is 20 to 80%.

3. The transparent conductive film according to claim 1 or 2, wherein: The transparent conductive film of indium-tin composite oxide includes 0.5 to 10% by mass of tin oxide, the thickness of the transparent conductive film of indium-tin composite oxide is 10 to 30 nm, the three-dimensional surface roughness SRa of the transparent conductive film of indium-tin composite oxide is 1 to 100 nm, the thickness distribution of the transparent conductive film in the width TD direction is 5% or less, In the evaluation of the thickness distribution in the width TD direction of the transparent conductive film, The transparent conductive film roll was cut into 50 mm in the length MD direction, and the thickness of the cut film was measured every 50 mm in the width TD direction from the end in the width TD direction until the opposite end. The thickness distribution of the transparent conductive film was calculated using Formula 2: In addition, the distance between the opposite end and the measurement point one point before it is less than 50 mm. [(maximum value of the thickness of the transparent conductive film)-(minimum value of the thickness of the transparent conductive film)]÷(maximum value of the thickness of the transparent conductive film)×100 (Formula 2).

4. The transparent conductive film according to any one of claims 1 to 3, wherein On the surface of the transparent conductive film, the transparent conductive film does not peel off in the adhesion test (JIS K5600-5-6: 1999), The indium-tin composite oxide transparent conductive film side was subjected to a bending resistance test (JIS K5600-5-1:1999), and when the bent portion was observed with a 10-fold magnifying glass, the mandrel diameter at which cracks or peeling occurred was less than 20 mm.

5. The transparent conductive film according to any one of claims 1 to 4, wherein The thickness of the transparent conductive film is 100 to 250 μm.

6. The transparent conductive film according to any one of claims 1 to 5, wherein A curable resin layer is provided between the transparent conductive film of indium-tin composite oxide and the transparent plastic film substrate.

Citation Information

Patent Citations

  • Transparent conductive laminate for touch panel

    JP2004071171A

  • Transparent conductive film and touch panel

    CN102165535A

  • Transparent conductive film

    CN103839607A